Reflections on Human Nature - Lovejoy, Arthur O. (Johns Hopkins University Press, 2020)
Originally published in 1961. Arthur O. Lovejoy, beginning with his book The Great Chain of Being, helped usher in the discipline of the History of Ideas in America. In Reflections on Human Nature, Lovejoy devotes particular attention to influential figures such as Hobbes, Locke, Bishop Butler, and Mandeville, tracing developments and changes in the concept of human nature through the seventeenth and eighteenth centuries. He also discusses the theory of human nature held by the founders of the American Constitution, giving special attention to James Madison and the "Federalist Papers."